Transformações nos saberes profissionais para ensinar aritmética na escola normal de São Luís - MA (1890 a 1952) - Cruz, Maria do Carmo Alves da (2022)
This research aimed to analyze historically the changes in professional knowledge to teach arithmetic at Escola Normal of São Luís/MA, from 1890 to 1952. This period was chosen because it was the time interval between the institutionalization of teacher training in Maranhão, with the creation of the Escola Normal, in 1890, and the advent of the Pedagogy course, in São Luís, in 1952. We seek to answer the following question: what changes took place in professional knowledge to teach arithmetic at the Escola Normal de São Luís/MA, from 1890 to 1952?. In order to do so, we make use of the theoretical-methodological contribution of authors who deal with Socio-Historical researches and who place systematized and objectified knowledge in a central position in the study of professional knowledge of the teacher who teaches mathematics, of researches related to the historian's craft and cultural history, and of authors who contribute to the expansion of research in the history of mathematics education. In the constitution of the sources, we list the educational legislation of the time, teaching programs, newspapers, books and official letters. The analyzes characterize professional knowledge to teach arithmetic in the Escola Normal, according to the pedagogical vacancy adopted. In this way, it was possible to identify two variants of professional knowledge: one to teach intuitive arithmetic and the other to teach tailored arithmetic.